ENVIRONMENTAL ETHICS AS A PHILOSOPHICAL PARADIGM OF LIFE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
In this scholarly article, the author examines ecological ethics from both philosophical and practical perspectives, analyzing how it shapes the principles of interaction between humans and nature, moral responsibility, ethical values, and life orientation. The author emphasizes the necessity of transforming ecological ethics from a theoretical concept into a practical behavioral model, as well as the importance of integrating an individual’s personal life strategy, social responsibilities, and civilizational development goals. The limitations of consumer culture, the role of moral ideals, and the intellectual development of individuals are considered not only within philosophical and social contexts but also in terms of the civilizational and cultural significance of ecological ethics. Furthermore, the article highlights the role of ecological thinking in building a sustainable, harmonious, and just human life.
Keywords: ecological ethics, civilization, strategy, morality, responsibility, culture, model